Complex distribution patterns of di-, tetra-, and hexaploid cytotypes in the European high mountain plant Senecio carniolicus (Asteraceae) - Suda, Jan; Weiss-Schneeweiss, Hanna; Tribsch, Andreas; Schneeweiss, Gerald M; Trávnícek, Pavel; Schönswetter, Peter (American journal of botany, 2007)
DNA ploidy levels were estimated using DAPI-flow cytometry of silica-dried specimens of the European mountain plant Senecio carniolicus (Asteraceae), covering its entire distribution area in the Eastern Alps (77 populations, 380 individuals) and the Carpathians (five populations, 22 individuals). A complex pattern of ploidy level variation (2x, 4x, 5x, 6x, and 7x cytotypes) was found in this species, which has been considered uniformly hexaploid. Hexaploids predominated in the Eastern Alps and was the only cytotype found in the Carpathians, while odd ploidy levels (5x, 7x) constituted a small fraction of the samples (<1.3%). Tetraploids occurred in two disjunct areas, which correspond with putative Pleistocene refugia for silicicolous alpine plants. Diploids occurred in large portions of the Alps but were absent from areas most extensively glaciated in the past. Intrapopulational cytotype mixture was detected in 22 populations-the majority involving diploids and hexaploids-with intermediate ploidy levels mostly lacking, suggesting limited gene flow and the evolution of reproductive isolation. Significant and reproducible intracytotype variation in nuclear DNA content was observed. Higher genome size in western diploids might be due to ancient introgression with the closely related S. incanus or to different evolutionary pathways in the geographically separated diploids.